Health care needs in patients with dementia and/or alzheimer’s: a comprehensive review - Alvarado García, Alejandra María; Alvarado Hueso, Paula Vanessa; Rojas Méndez, Laura Tatiana; Oviedo Tao, Paula Andrea (Revista Cuidarte, 2019)
Introduction: This study aims to identify scientific evidence related to the health care needs of patients with dementia and/or Alzheimer’s disease in Latin America. Materials and Methods: A comprehensive review of the scientific evidence was carried out following the Ganong’s methodology to search in the Embase, Ovid, PubMed, ProQuest, SciELO, ISI Web of Science and Scopus, REDALyC databases for articles published from 2012 to 2019. Results: 20 articles were included as the result of primary qualitative and quantitative research. The following categories are presented and discussed as findings: physical care needs, psychological care needs, and social care needs. Discussion and Conclusions: In the Latin American context, there is a knowledge gap on the research oriented to patients with dementia and/or Alzheimer’s disease. Recognizing the health care needs of patients with dementia becomes a priority for health professionals since providing an appropriate intervention promotes the quality of life of patients and their caregivers. How to cite this article: Alvarado AM, Alvarado PV, Rojas LT, Oviedo PA. Necesidades de cuidado en los pacientes con demencia y/o alzheimer: una revisión integrativa. Rev Cuid. 2019; 10(3): e813. http://dx.doi.org/10.15649/cuidarte.v10i3.813